Anti-inflammatory secondary metabolites from the stems of Millettia dielsiana Harms ex Diels. (1st October 2019) - Dat, Le Duc; Tu, Nguyen Thi Minh; Duc, Ngo Viet; Luyen, Bui Thi Thuy; Huyen, Chu Thi Thanh; Jang, Hyun Jae; Thu, Dang Thi; Huong, Tran Thu; Tram, Le Huyen; Thong, Nguyen Van; Hung, Nguyen Duc; Kim, Young Ho; et al.
Abstract: A phytochemical investigation for the constituents of the stems of Millettia dielsiana Harms ex Diels resulted in the isolation of a new isoflavone glycoside, mildiside A (1 ), and 14 known compounds (2 –15 ). Their chemical structures were determined using a combination of IR, NMR, MS, and optical rotation analysis, as well as comparison with the literature data. The ethanolic (EtOH) extract and several isolated compounds exert the inflammatory effect of nitric oxide (NO) production in lipopolysaccharide (LPS)-stimulated murine RAW264.7 macrophage cells. Graphical abstract: Image 1 Highlights: Structures of 15 phenolic derivatives including one new isoflavone glycoside, were isolated from the stems of Millettia dielsiana Harms ex Diels. The structure of a new compound was elucidated by 1D and 2D NMR spectra, MS data, and acid hydrolysis, together with HPLC analysis experiments. All the isolated compounds were evaluated for their inhibition of NO production in LPS-induced RAW264.7 cells.